Chinese herbal medicine Kuntai capsule for treatment of menopausal syndrome: a systematic review of randomized clinical trials. (December 2016) - Zhou, Quan; Tao, Jing; Song, Huamei; Chen, Aihua; Yang, Huaijie; Zuo, Manzhen; Li, Hairong
Highlights: Menopausal syndrome has an impact on women's quality of life and health problems. HRT is becoming more problematic in the management of menopausal symptoms. Kuntai capsule may be effective for treating menopausal syndrome. Kuntai capsule have lower risk of side effects than HRT for menopausal symptoms. Abstract: Objectives: Kuntai capsule has been widely used for the treatment of menopausal syndrome in China for long time. We conducted this review to assess efficacy and safety of Kuntai capsule for the treatment of menopausal syndrome. Methods: We searched studies in PubMed, ClinicalTrials, the Cochrane Library, China National Knowledge Infrastructure Database(CNKI), China Science and Technology Journal Database (VIP), Wan fang Database and Chinese Biomedical Literature Database(CBM) until November 20, 2014. Randomized trials on Kuntai capsule for menopausal syndrome, compared with placebo or hormone replacement therapy (HRT) were included. Two reviewers independently retrieved the randomized controlled trials (RCTs) and extracted the information. The Cochrane risk of bias method was used to assess the quality of the included studies, and a Meta-analysis was conducted with Review Manager 5.2 software. Results: A total of 17 RCTs (1455 participants) were included. The studies were of low methodological quality. Meta-analysis indicated that there was no statistical difference in the Kupperman index (KI) [ WMD  = 0.51, 95% CI (−0.04, 1.06)], the effective rate of KI [ OR  = 1.21, 95% CI (0.72, 2.04)], E2 level [ WMD  = −15.18, 95% CI (−33.93, 3.56)], and FSH level [ WMD  = −3.46, 95% CI (−7.2, 0.28)] after treatment between Kuntai versus HRT group (P  > 0.05). However, Compared with HRT, Kuntai capsule could significantly reduce the total incidence of adverse events [ OR  = 0.28, 95% CI (0.17, 0.45)]. Conclusions: Kuntai capsule may be effective for treating menopausal syndrome and lower risk of side effects. The studies we analyzed were of low methodological quality. Therefore, more strictly designed large-scale randomized clinical trials are needed to evaluate the efficacy of Kuntai capsule in menopausal syndrome.